Decentralized Adaptive Sliding Mode Control of Large-Scale Semi-Markovian Jump Interconnected Systems With Dead-Zone Input - Jiang, Baoping; Gao, Cunchen (IEEE transactions on automatic control, 2022)
In this article, a decentralized adaptive sliding mode control scheme is proposed for stabilization of large-scale semi-Markovian jump interconnected systems, in which dead-zone linearity in the input and unknown interconnections among subsystems are tackled. First, by designing an integral sliding surface for each subsystem, local sliding mode dynamics are obtained in good property of dynamics. Second, sufficient conditions are established for checking the stochastic stability of the sliding mode dynamics with generally uncertain and unknown transition rates. Third, a variable structure controller is designed to guarantee finite-time reachability of sliding surface, and the unknown interconnections among subsystems are compensated by adaptive laws. Finally, a numerical example is provided to verify the effectiveness of the proposed control scheme.